(untitled) (Nepalese Journal of Radiology, 2020)
Introduction: The pituitary gland is the master endocrine gland that secretes important hormones and controls other glands. Its size, shape and volume vary with age and sex and also in various pathological conditions. This study was conducted to identify the size, shape and volume of the normal pituitary gland in different age groups of both genders using Magnetic Resonance Imaging (MRI). Methods: A retrospective study of the brain MRI Images of 203 patients was done in the Radiology and Imaging department of Pokhara Academy of Health Sciences, Nepal. Anterior-posterior dimension, transverse dimension, height and shape of the pituitary gland were noted and volume was calculated. Descriptive analysis and relationship of pituitary parameters with age and sex were assessed using ANOVA and Chi-square tests. Results: The pituitary height and volume was maximum in the 11-20years age group. Similarly, the mean height and volume of the pituitary gland in female patients of each age group were greater than that of male patients in the same age group. The inferential analysis revealed significant differences for mean pituitary height and volume with age but not with gender. The upper surface convexity was maximum in the age group 11-20years. Conclusion: The study has shown a clear trend with regards to the morphology of the pituitary gland with the age and sex of the individual highlighting the size, shape and volume of the pituitary gland should be taken into consideration while evaluating the glands for any neuroendocrine disorders.